Bibliometric analysis on bitcoin 2015-2020 / Nurazlina Abdul Rashid ... [et al.] - Abdul Rashid, Nurazlina; Bosli, Fazillah; Abdul Rahim, Amirah Hazwani; Kasim, Kartini; Ahmad@Ahmad Jali, Fathiyah (2021)
This paper analyzes and reports on various types of bitcoin-related published works. This study used a bibliometric analysis, to analyze the evolution of bitcoin research by examining document profile and research trend. Based on the keyword search result, this study had analyzed finalized 1,680 documents from the Scopus database online as of Feb 2021. This study reported that the standard bibliometric indicator to identify research activity on bitcoin between the years 2015 and 2020. The analysis was carried out using Microsoft Excel, Harzing's Publish and Perish software, and the biblioshiny of R studio. From its inception in 2008, Bitcoin has garnered a lot of attention from the academic world, both in the West and East. Within a decade, many academic publications have been produced over Bitcoin. Our findings will give vital insights into improving the Bitcoin's inclusivity and global reach.